MicroRNAs 155 and 125b Physiologically and Pathologically Regulate Hematopoiesis and Immunity - Chaudhuri, Aadel Ahmed (California Institute of Technology, 2012)
MicroRNAs are a class of ~22 nucleotide RNA molecules with roles in diverse biological processes. Here I focus on two microRNAs, miR-155 and miR-125b, and reveal pathways by which their dysregulation leads to myeloproliferative disorder (MPD) and leukemia, respectively. I begin by searching for miR-155 target genes relevant to MPD. By writing an algorithm to search microarray data for predicted microRNA target genes, I identified 89 candidate target genes for miR-155 in myeloid cells. Literature search whittled this list down to 11, and one gene among them, SHIP1, turned out to be largely responsible for miR-155’s ability to cause MPD. My focus shifted to miR-125b when I noticed that miR-125b was enriched in macrophages and thus might play important roles in that cell type. Indeed, gain- and loss-of-function experiments indicated that miR-125b is a potent activator of macrophage activation, and I identified IRF4 as the primary target gene in this process. Finally I asked whether miR-125b plays pathophysiological roles in the development of the hematopoietic system. Thus I overexpressed miR-125b in the hematopoietic system and, to my surprise, observed a very aggressive myeloid leukemia capable of infiltrating peripheral organs including the lungs, liver, kidneys and brain. To determine whether miR-125b is physiologically necessary for normal hematopoietic development, I designed a loss-of-function sponge vector that acts as a decoy, attracting the microRNA away from its normal targets. Use of the sponge in the mouse hematopoietic system led to significantly decreased overall hematopoietic ouput, indicating that miR-125b is physiologically required for normal hematopoiesis. Next, I assayed in vitro a panel of miR-125b target genes and saw that one, Lin28, was superior to the rest. Indeed, Lin28 gain- and loss-of-function in vivo recapitulated major aspects of miR-125b loss- and gain-of-function, respectively. Thus I identified Lin28 as a primary target of miR-125b in the hematopoietic system. In summary, my work shows that two microRNAs, miR-155 and miR-125b, physiologically and pathologically control hematopoietic development. I also identify important target genes for each of these microRNAs in their respective disease processes. Indeed, therapeutic targeting of these pathways may prove useful in the treatment of cancer.
Keywords: myeloproliferative disorder; microRNA; hematopoietic stem cell; mir-125b; hematopoiesis; immune system; leukemia; mir-155; Biology; macrophage